Finite-time control strategy for swarm planar underactuated robots via motion planning and intelligent algorithm - Zixin Huang; Shaoqi Wei; Mengyu Hou; Lejun Wang (Measurement + Control, 2023)
The swarm planar underactuated robots have the ability to organize each robot to complete task in a finite time and the characteristics of ignoring gravity, energy saving, light weight, and so on. In this paper, we propose control strategy for such robot via motion planning and intelligent algorithm. First, we establish a unified dynamic model and analysis its underactuated characteristics. In order to enable all links to reach the target position smoothly in a finite time, a suitable trajectory is planned and parameters are optimized by the differential evolution algorithm (DEA). Then, the controllers are designed for each planar underactuated robot. Finally, the simulation results show that the proposed strategy is effective.